PREFERENSI DAN KERUSAKAN TUMBUHAN KOLEKSI KEBUN RAYA CIBODAS OLEH BENALU Scurrula oortiana (Korth.) Dans. - Sunaryo Sunaryo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
The mistletoe of Scurrula oortiana (Korth.) Dans. (Loranthaceae) growing on several collection plants at Cibodas Botanical Garden. The mistletoe parasite 48 species of plants collection, what come within in 24 tribe. Plants collection which attacked as the highest is group of Ficus type (Moraceae). While attacked by individual in number at most is Callistemon citrinus (Myrtaceae). The mistletoe has caused the damage at part of branch. Infected and uninfected branches of host species were observed. The result showed that the mistletoe causes degradation of the distal part of the infected branches. Damage value of branch which parasite of mean more than 50%.